Low methyl-esterified pectin protects pancreatic β-cells against diabetes-induced oxidative and inflammatory stress via galectin-3. (1st December 2020) - Hu, Shuxian; Kuwabara, Rei; Beukema, Martin; Ferrari, Michela; de Haan, Bart J.; Walvoort, Marthe T.C.; de Vos, Paul; Smink, Alexandra M.
Highlights: Pectins prevent pancreatic β-cell damage during oxidative and inflammatory stress. Pectin with lower DM value is more efficacious than higher-DM pectins in protection of β-cell for stress. Low-DM Pectin protects β-cell through protecting mitochondria for toxin and cytokine induced dysfunction. The protective effect of pectin depends on the receptor galectin-3. Abstract: Insufficient intake of dietary fibers in Western societies is considered a major contributing factor in the high incidence rates of diabetes. The dietary fiber pectin has been suggested to be beneficial for management of both Diabetes Type 1 and Type 2, but mechanisms and effects of pectin on insulin producing pancreatic β-cells are unknown. Our study aimed to determine the effects of lemon pectins with different degree of methyl-esterification (DM) on β-cells under oxidative (streptozotocin) and inflammatory (cytokine) stress and to elucidate the underlying rescuing mechanisms, including effects on galectin-3. We found that specific pectins had rescuing effects on toxin and cytokine induced stress on β-cells but effects depended on the pectin concentration and DM-value. Protection was more pronounced with low DM5 pectin and was enhanced with higher pectin-concentrations. Our findings show that specific pectins might prevent diabetes by making insulin producing β-cells less susceptible for stress.